OILS OF THE GERASIMOVKA FIELD (TOMSK REGION) - Badmayeva Z.O.; Vyshemirskiy V.S.; Pertseva A.P.; Ryzhkova S.M.; Doil'nitsyn E.F. (My University, 1988)
Oil flows, sometimes fairly intensive, were observed in many exploratory wells drilled in middle Paleozoic carbonates of the Paleozoic Nyurol'skiy sedimentary basin, located in the southwestern part of the Tomsk region and extending southward into the Novosibirsk region. The genesis of the oil in these strata remains debatable, even though the first oil flow from the Paleozoic was observed more than 20 years ago. We use data on oil of the Gerasimovka field, located on the eastern edge of the Nyurol' skiy basin, to settle this controversial question. Our comparison of Gerasimovka oils with the Ostaninskiy and Kalinovoye oils suggests that all the Gerasimovka oils are genetically associated with Paleozoic rocks.
Keywords: Paleozoic; Paleozoic; Палеозой